(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2025)
The aim of this research was to investigate the influence of overconfidence on managers’ strategic choices, through a qualitative case study conducted with the Algerian state-owned company ENIE. Interviews were conducted with 8 executives to explore their perceptions of their decision-making process. The analysis revealed the presence of numerous cognitive biases, such as overconfidence, loss aversion and historical anchoring, and their potentially harmful impact on strategic decisions. These results confirm the value of studying these biases to improve decision-making. However, the absence of a quantitative phase is a methodological limitation. Future research should replicate this type of study using mixed methods. Despite these reservations, this research sheds relevant light on the influence of cognitive biases in strategic choices within complex organizations, and highlights the need to raise awareness among decision-makers. Keywords: Cognitive biases, Overconfidence, managerial decision making.